Simultaneous Realization of Wavelength Conversion, 2R Regeneration, and All-Optical Multiple Logic Gates with OR, NOR, XOR, and XNOR Functions Based on Self-Polarization Rotation in a Single SOA: An Experimental Approach. (26th April 2012) - Said, Youssef; Rezig, Houria
Abstract : We highlight the feasibility of experimental implementation of both inverted and noninverted wavelength conversion, 2R regeneration, and all-optical logic functions, such as OR, NOR, XOR, and XNOR optical gates by exploiting the self-polarization rotation in a semiconductor optical amplifier (SOA) device without changing the setup configuration. Switching between each optical function is done by only adjusting the input optical power level. In order to allow optimum control and preserve the polarization state of the injected and collected signals, the polarimetric measures have been carried out in free space.